Community-Based Urban Violence Prevention Innovative Approaches in Africa, Latin America, Asia and the Arab Region (Edition 1) - Matuk, Silvia; Mathéy, Kosta (transcript Verlag, 2014)
Urban violence has become a major threat in big cities of the world. Where the orthodox protection through the police and individual target hardening remain inefficient, the population must organize itself.This book contains first-hand accounts on a selection of the most innovative experiences in Africa, Latin America, Asia and the Arab region and is of interest likewise for academics and urban practitioners, policy makers, international cooperation experts or travelers preparing a visit of one of the affected countries.With a preface by Caroline Moser.